Beginning Silverlight 3 : from novice to professional - Lair, Robert (New York : Apress, 2009)
Provides information on ways to create interactive Web applications using Silverlight 3, "a Microsoft cross-browser, cross-platform plug-in that allows you to created rich interactive (or Internet) applications (RIAs) for the Web"-- P.1.
Includes index.
"Learn to build state-of-the-art Silverlight applications quickly and easily"--P. 1 of cover.
Keywords: Multimedia systems; Application software -- Development; Web site development